Pemodelan Determinan Penerimaan Pajak Penghasilan Dari Orang Pribadi Pelaku UMKM Menggunakan Causal Loop Diagram - Murtadho, Muhammad Afif; Achsani, Noer Azam; Alexandi, Muhammad Findi (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The large number of Micro, Small and Medium Enterprises (MSMEs) that make a significant contribution to gross domestic revenue shows that MSMEs have a very vital role in the Indonesian economy. However, tax revenues originating from MSMEs are still far from what they should be. Based on these conditions, this study aims to: (a) identify the determinants of income tax revenue from individual MSME taxpayers; (b) create a causal loop diagram on the determinants of income tax revenue from individual taxpayers of SMEs; (c) provide alternative strategies in the context of increasing state revenue from income taxes originating from individual taxpayers of MSME actors. To obtain the variables in order to build the model, literature studies and interviews were carried out, then the causal loop diagram (CLD) model was built using Vensim software. The results of the study indicate that in an effort to collect optimal state revenues, a strategy is needed that can balance the frequency of various internal programs at DGT, especially related to aspects of tax extensification, monitoring and socialization activities. Keywords: causal loop, income tax, individual, MSMEs, taxpayer